Uniting the Uteri: A Case Series (Global Journal of Medical Research, 2023)
Background Metroplasty is a reconstructive surgery to repair congenital anomalies of the uterus Anomalous uteri are known to cause infertility and recurrent abortions due to defective implantation restrictive foetal growth and malpresentations Aim To discuss our experiences and surgical techniques with various cases of metroplasty in women with structural uterine anomalies with infertility or recurrent abortions at a tertiary care hospital in Mumbai Case description A descriptive study of case series of metroplasty conducted in a tertiary care hospital in women with bicornuate and didelphys uterus by opening the uterine cavities by incision on the medial aspect of the hemicolpos and approximating the myometrial edges and suturing them to create a single uterine cavity
Keywords: metroplasty; mullerian anomalies; vaginoplasty; bicornuate uterus; uterine didelphys; recurrent pregnancy loss